Early diagnosis of atypical rupture of scarred uterus: A case Report from Rural Nepal - Dangal, Binod; Gupta, Tula Krishna; Pathak, Santosh; Upreti, Arun; Acharya, Bibek; Diwakar, Uday (Journal of General Practice and Emergency Medicine of Nepal, 2020)
A 28 years female from rural municipality of Dolakha was referred to our center diagnosis of G2P1 at 40 weeks of gestation in active stage of labor with previous CS. With the view of symptoms and history of previous CS, patient was shifted to Operation Theatre for delay in latent stage of labor, ruptured uterus identified at operating table and Caesarian Hysterectomy was done. Her post-operative hospital stay was uneventful. Spontaneous silent rupture can occur in women without any alarming symptom. Rapid recognition of potential uterine rupture and immediate laparotomy lower the rate of perinatal death.